Investigations of tungsten carbide nanostructures treated with different temperatures as counter electrodes for dye sensitized solar cells (DSSC) applications - Vijayakumar, P.; Senthil Pandian, M.; Lim, S.P.; Pandikumar, A.; Huang, N.M.; Mukhopadhyay, S.; Ramasamy, P. (Kluwer (now part of Springer), 2015)
Tungsten carbide (WC) materials are synthesized and sintered at 800, 900 and 1000 °C. The differently treated tungsten carbide nanostructures (WC-NSs) have been investigated as counter electrode (CE) catalysts to replace the expensive platinum (Pt) for dye sensitized solar cells (DSSC) towards better power conversion efficiency. The synthesized samples were structurally characterized by powder X-ray diffraction (PXRD) which reveals that the sintering temperatures strongly affect the structure of WC-NSs. The surface morphology and chemical compositions were examined by scanning electron microscope (SEM) fitted with energy dispersive X-ray analysis (EDAX). The electrochemical studies of WC-NSs suggest that increasing the sintering temperature leads to increase in the charge transfer resistance and results in decrease of the catalytic activity of the WC-NSs CE. The power conversion efficiency of the WC-NSs materials sintered at 800 °C is higher than that of 900 °C and 1000 °C sintered materials. It is found that the photovoltaic performance was strongly affected by the sintering temperature of the WC-NSs materials. The tungsten carbide nanorods sintered at 800 °C showed better photovoltaic parameters such as Jsc, Voc, FF and η of 2.71 mA cm−2, 0.53 V, 0.28 and 0.41 %, respectively when compared to the WC-NSs sintered at 900 and 1000 °C. The optimally modified WC-NSs could be a useful substitute.